PELATIHAN BAHASA JEPANG BISNIS DI PT. FUKURYO SEMARANG - Elizabeth Ika Hesti Aprilia Nindia Rini; Yuliani Rahmah (Departemen Linguistik, Fakultas Ilmu Budaya Universitas Diponegoro, 2021)
The purpose of this community service activity is to introduce the culture and various conversations used in business, especially in Japanese companies. This training is used to support performance, especially in terms of communication for Indonesian workers who work in Japanese companies. Through this community service activity, workers can optimize performance with the ability to speak Japanese everyday, especially to communicate in the work environment, both with workers from Japan, and with guests from Japan. In addition, through this business Japanese training, it is hoped that workers in Japanese companies will have the confidence to communicate in Japanese so that they can improve the quality and competence of human resources so as to support company productivity.